2002
DOI: 10.1038/sj.jhh.1001449
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure monitoring in haemodialysis and continuous ambulatory peritoneal dialysis (CAPD) patients

Abstract: The aim of this study was to compare the results of the 44-h ambulatory blood pressure monitoring (ABPM) data between haemodialysis (HDp) and CAPD patients and to investigate the relation of circadian rhythm in blood pressure (BP) with development of left ventricular hypertrophy. Twenty-two HDp (11 male, 11 female, mean age: 50 ± 17 years) and 24 CAPDp (11 male, 13 female, mean age: 47 ± 15 years) were included. Echocardiographic measurements and ABPM were performed in all study groups. ABPM of the first and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…The BP profile of the study population displayed the com- mon characteristics of predominance of nondippers that has been described in patients with chronic kidney disease and patients who are on dialysis (27)(28)(29)(30). BP control was satisfactory at baseline, and the enhancement of UF with icodextrin did not result in any changes in BP control or in the circadian behavior of BP levels.…”
Section: Discussionmentioning
confidence: 69%
“…The BP profile of the study population displayed the com- mon characteristics of predominance of nondippers that has been described in patients with chronic kidney disease and patients who are on dialysis (27)(28)(29)(30). BP control was satisfactory at baseline, and the enhancement of UF with icodextrin did not result in any changes in BP control or in the circadian behavior of BP levels.…”
Section: Discussionmentioning
confidence: 69%
“…13 In another study, the comparison of 22 patients on HD with 24 patients on PD with 44-hour ambulatory BP monitoring showed no differences in daytime and nighttime BP. 14 Nonetheless, highquality head-to-head studies are sparse and the epidemiology of hypertension may be similar to that seen among HD patients. 15 Among PD patients, volume excess, as assessed by tracer dilution, was common and was related to DBP and eccentric left ventricular hypertrophy (LVH).…”
Section: Epidemiology Of Hypertension In Peritoneal Dialysismentioning
confidence: 99%
“…However, in the measurement of LVH, formulas are applied that rely heavily on the cube root of end diastolic diameter [43], so that small differences in hydration status have substantial impacts on the obtained values. With regard to blood pressure control, 44 h blood pressure monitoring has shown that hypertension is less prevalent in HD than in PD patients on the day of dialysis but on the second day, is more prevalent and more expressed [44].…”
Section: Dialysis Modality and De Novo Cardiac Diseasementioning
confidence: 99%